FOSTERING RELIGIOUS HARMONY THROUGH ISLAMIC BOARDING SCHOOLS AT ISLAMIC BOARDING SCHOOLS DARUSSHOLAH IV AND DALILUL KHOIROT AN-NAWAWI BANGKA BELITUNG - Dewi, Ratna; Ansori, Muslim (State Islamic University North Sumatra, 2023)
Abstract: This research aims to find out the fostering of religious harmony, the values of harmony and the obstacles faced by religious people through pesantren in Darussholah IV and Dalilul Khoirot An-Nawawi Islamic boarding schools in Bangka Belitung. This research is a descriptive qualitative research using a phenomenological approach. The results of this study are: cooperation in religious activities, as well as cooperation in social service activities. While the values of religious harmony are: the value of unity, ta'aruf